Developing Culturally Responsive Augmented Reality Pop-Up Books for Elementary Social Studies: A Preliminary Needs Analysis - Ruliani, Epit; Nasution, Nasution; Rachmadyanti, Putri (Journal of Innovation and Research in Primary Education, 2025)
Contemporary Social Studies instruction in elementary schools faces significant challenges in engaging students with cultural heritage content, primarily due to teacher-centered approaches and limited interactive media. This study addresses the need for innovative, culturally responsive instructional media by conducting a preliminary needs analysis for developing Augmented Reality (AR) Pop-Up Book embedded with ethnopedagogical content. A qualitative descriptive approach was employed at SDN Sawunggaling I/382 Surabaya, involving one fifth-grade teacher and ten students. Data were collected through classroom observations, semi-structured interviews, and document analysis, then analyzed using Miles and Huberman's interactive model. Findings revealed persistent lecture-dominated instruction with minimal interactive media utilization, resulting in low student engagement and suboptimal learning outcomes. Both teachers and students expressed strong need for interactive, visual media that contextualizes cultural heritage content. Current instructional resources proved inadequate for facilitating meaningful engagement with abstract cultural concepts. The identified needs strongly support AR Pop-Up Book development as an appropriate pedagogical solution. Integration of AR technology with ethnopedagogical principles can address engagement challenges while strengthening cultural identity. Findings align with research demonstrating AR's effectiveness in improving motivation and learning outcomes, while ethnopedagogy enables authentic connections between academic content and lived cultural experiences.